Transforming Tropical Crops: Postharvest Processing and Enterprise Viability of MaCoMa Coffee Blend in Davao Oriental, Philippines - Leal, Imelda; Ramos, Lovelyn M.; Ma-ata, Mar Fe S.; Micutuan, Catherine; Pieza, Jelian; Gutana, Katrina B. (Department of Agronomy and Horticulture, IPB University, 2025)
This study explored the development of a novel, non-caffeinated coffee alternative using underutilized tropical crops: marang seeds (Artocarpus odoratissimus), corn (Zea mays), and malunggay (Moringa oleifera) leaves. These crops are abundant in tropical regions, such as Banaybanay, Davao Oriental, Philippines, yet remain largely untapped for value-added food products. Marang, a seasonal fruit native to the Philippines, yields seeds rich in protein, fats, and carbohydrates, which are often discarded as waste. Corn, widely cultivated in the region, contributes dietary fiber and antioxidants, while malunggay leaves are celebrated for their dense micronutrient content, including iron, calcium, and vitamins A and C. The MaCoMa (Marang + Corn + Malunggay) coffee blend was formulated through strategic post-harvest processing techniques, including roasting, drying, and blending, to enhance flavor, preserve nutrients, and extend shelf life. The research evaluated both scientific parameters, such as nutritional profiling and sensory attributes (appearance, aroma, taste, and texture), as well as business viability factors, including consumer acceptability and financial metrics. A sensory evaluation conducted with 200 respondents revealed high levels of acceptability, particularly in terms of aroma and taste. Economic analysis indicated a Return on Investment (ROI) of 7.84%, a net profit margin of 6.86%, and a payback period of 1.5 years, evidence of strong enterprise potential. A SWOT analysis highlighted key strengths, including local availability, nutritional benefits, affordability, and sustainability, while also noting challenges such as limited market awareness and shelf-life constraints. This project demonstrates the potential of transforming tropical crops into market ready products that support community-based enterprises. The MaCoMa coffee blend offers a healthier alternative to conventional coffee, promotes agricultural innovation, reduces postharvest waste, and creates livelihood opportunities. Continued research into flavor variants, shelf-life stabilization, and regional marketing is recommended to scale its impact across tropical agricultural communities.